Evaluation of using Recombinant Human Bone Morphogenetic Protein-2 (rhBMP-2) in post extraction dental socket preservation < Clinical and radiological study> - نايف, محمد; حكمت يعقوب , (Latakia University Journal -Medical Sciences Series, 2024)
Background: Changes in alveolar bone dimensions following tooth extraction over time are inevitable. Bone resorption and poor bone quality make the placement of dental implants difficult. Oral health care procedures around implants become more difficult and the result is poor both cosmetically and functionally. Therefore, several methods and techniques aimed at reducing or preventing bone resorption, preserving socket, and improving the quality of regenerated bone include autografts, allografts, xenografts, growth factors, and biomaterials. Bone morphogenetic proteins (BMPs) belong to transforming growth factor beta (TGF-β) and are biological factors that play important roles in bone formation process and can significantly increase bone regeneration and, as a result, can be used to preserve alveolar bone after tooth extraction. Aim: Evaluate the effectiveness of applying rhBMP-2 locally in order to maintain alveolar bone dimensions after dental extraction, and evaluate the density of bone formed at the extraction site after applying rhBMP-2 using CBCT. Materials and Methods: Written consent was obtained from each patient who had an indication for bilateral tooth extraction in the same jaw and the same number of roots on both sides. Then, sterilization of the oral fossa, local anesthesia, and separation of the connective ligament from the teeth to be extracted were performed. Then the teeth to be extracted were removed using root levers and clamps with as little trauma as possible, and then the tooth to be extracted was applied. After that we choose a side to apply Gelfoam impregnated with rhBMP-2 liquid (right side or left side) in a simple random manner by withdrawing a paper specifying the study side and in the corresponding control side we applied Gelfoam alone as a hemostatic agent. after which suturing was performed on the extraction sites in both groups, then an x-ray image was taken using cone beam computed tomography. CBCT after the surgical procedure. Results: The use of rhBMP-2 to preserve the socket after extraction reduced the amount of bone resorption that occurred after extraction, both horizontally and vertically, after a follow-up period of three months, but did not completely prevent it from occurring. Using it to preserve the socket immediately after extraction did not significantly improve radiographic bone density compared to the control group in which Gelfoam was applied alone as a hemostatic agent after a follow-up period of three months.